GC-MS ANALYSIS OF BIOACTIVE COMPOUNDS, ANTIOXIDANT AND ANTIBACTERIAL ACTIVITY OF ABUTILON INDICUM (L) LEAVES - S. V. Saranyaa; J. Dhanalakshmi (Kongunadu Research Journal, 2025)
The present study explored the therapeutic potential of A.indicum leaves. In today’s world, plant secondary metabolites are increasingly favored as therapeutic agents to address various diseases and disorders. This study aimed to analyze the bioactive secondary metabolite profile of A.indicum leaves by assessing the total alkaloid, phenolic, and flavonoid content, antioxidant capability, and properties of four aqueous and ethanolic extracts. Qualitative phytochemical analysis using different polarity solvents and established methods revealed the presence of alkaloids, flavonoids, phenols, steroids, tannins, saponins, phytosterols, terpenoids, and glycosides in the leaves. The antioxidant potential was evaluated using DPPH and ABTS radical scavenging assays, while spectrophotometric methods were employed to measure the total alkaloid, flavonoid, and phenolic contents in the leaf extracts. The ethanolic extract showed a higher yield, greater antioxidant potential, and elevated total phenolic and flavonoid contents compared to the aqueous extracts. Analysis of bioactive compounds using Gas Chromatography-Mass Spectrometry (GC-MS). Gas Chromatography-Mass Spectrometry (GC-MS) examination of ethanolic leaf extracts identified 36 chemical entities of both high and low molecular weight in different quantities. These bioactive chemical compounds have been shown to have physiological significance and are crucial from a pharmaceutical perspective. This study indicates that the leaves of A.indicum are rich in bioactive secondary metabolites that positively impact human health, possess strong antioxidant properties, and exhibit antibacterial activity against certain bacterial strains, highlighting their considerable therapeutic potential.